Temozolomide combined with irinotecan caused regression in an adult pleomorphic rhabdomyosarcoma patient-derived orthotopic xenograft (PDOX) nude-mouse model - Igarashi, Kentaro (Oncotarget, 2017)
Adult pleomorphic rhabdomyosarcoma (RMS) is a rare and recalcitrant, highly-malignant mesenchymal tumor in need of improved therapeutic strategies. Our laboratory pioneered the patient-derived orthotopic xenograft (PDOX) nude mouse model with the technique of surgical orthotopic implantation (SOI). We previously described the development of a PDOX model of adult pleomorphic RMS where the tumor behaved similar to the patient donor. A high-grade pleomorphic rhabdomyosarcoma from a striated muscle was previously grown orthotopically in the right biceps-femoris muscle of nude mice to establish the PDOX model. In the present study, the PDOX models were randomized into the following treatment groups when tumor volume reached 100 mm(3): G1, control without treatment; G2, cyclophosphamide (CPA) 140 mg/kg, intraperitoneal (i.p.) injection, weekly, for 3 weeks; G3, temozolomide (TEM), 25 mg/kg, per oral (p.o.), daily, for 21 days; G4, temozolomide (TEM) 25 mg/kg, p.o., daily, for 21 days combined with irinotecan (IRN), 4 mg/kg, i.p., daily for 21 days. After 3 weeks, treatment of PDOX with TEM combined with IRN was so powerful that it resulted in tumor regression and the smallest tumor volume compared to other groups. The RMS PDOX model should be of use to design the treatment program for the patient and for drug discovery and evaluation for this recalcitrant tumor type.